Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China - Xue, Qingquan; Mckamey, Stuart H.; Zhang, Yalin (Zootaxa, 2017)
A new genus of Idiocerinae, Philippogalla gen. nov., is described and illustrated based on Philipposcopus modestus (Baker) from the Philippines. A lectotype is designated for P. modestus. In addition, a new species Philipposcopus processus sp. nov. is described and illustrated from China.